Ensino socioambiental nas ciências contábeis - Feitosa, André Luís Oliveira (2018)
Nowadays, societies all over the world understand that economic organizations have higher obligations than merely providing the market with of goods and services. They are expected to minimize the social and environmental impacts that may result from their activities. The Social and Environmental Accountancy aims to measure, control and economically demonstrate the environmental assets and liabilities resulting from those impacts. Nevertheless, previous studies have found an obstacle to the operationalization of the social and environmental accountancy for professionals of the field. This condition may be a result of flaws of the teaching process, specifically with reference to the didactic content of this discipline. The thesis aims to investigate if the contents of social and environmental accountancy, contrary to traditional accountancy, are centered exclusively in the theoretical part of the discipline failing to promote practical teaching. The objective of this study is to analyze the characteristics of social and environmental teaching in Accounting Sciences and to enable new structures for teaching its contents. The Critical Analysis of a Speech was used as methodology to investigate the didactic pedagogical elements of the discipline of Social and Environmental Accountancy and the disciplines of Traditional Accountancy in Higher Education courses. It also aims to identify elements of didactic and methodological similarities and divergences that support our thesis and allow us to propose a solution to the presented issue, contributing to the development of accountancy in the social and environmental field, focusing on providing it with more theoretical development and means to its teaching and applicability.________________________________________________________________________________________________________________________________